2016
DOI: 10.3892/ol.2016.4919
|View full text |Cite
|
Sign up to set email alerts
|

MMP-14 and TGFβ-1 methylation in pituitary adenomas

Abstract: Abstract. Pituitary adenoma (PA) is one of the most common abnormalities in the sellar region. Despite the fact that PA is a benign monoclonal neoplasm, it can cause serious complications, including ophthalmological, neurological and endocrinological abnormalities. Currently, the causes that increase the progression of tumors are unknown. Epigenetic silencing of the matrix metalloproteinase-14 (MMP-14) and transforming growth factor beta-1 (TGFβ-1) genes may be associated with the development of PA, since thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It has been demonstrated that NNMT-mediated methylation is an important conjugation reaction in the biotransformation of a number of drugs and xenobiotics, including pyridine and other structurally-associated compounds (18). The epigenetic silencing of TGF-β1 genes is associated with the development of pituitary adenoma (33). In the present study, it was hypothesized that NNMT-mediated changes in DNA methylation may be involved in TGF-β-induced EMT in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 77%
“…It has been demonstrated that NNMT-mediated methylation is an important conjugation reaction in the biotransformation of a number of drugs and xenobiotics, including pyridine and other structurally-associated compounds (18). The epigenetic silencing of TGF-β1 genes is associated with the development of pituitary adenoma (33). In the present study, it was hypothesized that NNMT-mediated changes in DNA methylation may be involved in TGF-β-induced EMT in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 77%
“…Methylation and expression levels of the N-myc Downstream-Regulated Gene 2 (NDRG2) and Signal Transducer and Activator of Transcription 3 (STAT3) promoters are also uncorrelated, along with a lack of correlation with clinical factors (86, 87). Methylation of the Matrix Metallopeptidase 14 (MMP-14) and Transforming Growth Factor Beta 1 (TGF β -1) promoters was also not associated with tumor functionality or recurrence (88). Hypermethylation of the Human Telomerase Reverse Transcriptase (hTERT ) promoter, which can contribute to cellular immortalization and tumorigenesis, has also been noted across different pituitary tumor subtypes but has not been associated with significant differences in tumor parameters, tumor subtype, or prognosis (89).…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…It is affect DDR1 ligand combined with DDR1 can promote the DDR1 signaling pathway. DDR1 promotes MMP-2/9 expression, leading to ECM reconstruction and tumor invasion [25][26][27]. Cell apoptosis, change tumor cell invasiveness, and regulation of energy metabolism is mediated by hypoxic condition.…”
Section: Discussionmentioning
confidence: 99%